Avaliação da reposta imune por células polimorfonucleares e mononucleares humanas infectadas com formas promastigotas de Leishmania (Leishmania) amazonensis - Braga, Lais de Souza (2015)
The establishment of American cutaneous leishmaniasis (ACL) is determined by the species of the parasite, the saliva of the sandfly, and by the host immunity, involving neutrophils, macrophages, cytokines and costimulatory molecules. This work aimed to evaluate the immune response of neutrophils and monocytes isolated from the blood of healthy individuals, followed by infection with promastigotes of Leishmania (Leishmania) amazonensis. It was collected 8 mL of blood of 42 individuals without ACL history for the separation of mononuclear cells and polymorphonuclear cells. Cells were infected with L. (L.) amazonensis and tested for phagocytosis, production of nitric oxide and expression of IL-8, CXCR1, CCL3, CCR1 and iNOS. Neutrophils showed increased phagocytic activity and NO production in the early hours of infection in macrophages and end times of the infection, and the two cells showed expression of IL-8, CXCR1, CCL3, CCR1 and iNOS, but not statistically significant. The highest phagocytic activity and NO production by neutrophils in the early hours of infection and macrophages later show that these cells may be assisting in the induction of the immune response dichotomy.